2023
DOI: 10.3389/fonc.2023.1213426
|View full text |Cite
|
Sign up to set email alerts
|

Yes-associated protein-1 overexpression in ocular surface squamous neoplasia; a potential diagnostic marker and therapeutic target

Abstract: Yes-associated protein-1 (YAP-1) is a Hippo system transcription factor, which serves as an oncogene in squamous cell carcinoma, and several solid tumors when the Hippo pathway is dysregulated. Yet, the activity of YAP-1 in ocular surface squamous neoplasia (OSSN) has not been determined. Here, we investigate the relationship between YAP-1 overexpression and OSSN. Using a cross-sectional study design, we recruited 227 OSSN patients from the University Teaching Hospitals in Lusaka, Zambia. Immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
2
0
0
Order By: Relevance
“…High YAP1 expression was correlated with nuclear and cytoplasmic localization (hereinafter referred to as YAP1 high), while low YAP1 expression was correlated with cytoplasmic localization (hereafter referred to as YAP1 low). These findings are consistent with those of the previous report ( 20 , 21 ).…”
Section: Resultssupporting
confidence: 94%
“…High YAP1 expression was correlated with nuclear and cytoplasmic localization (hereinafter referred to as YAP1 high), while low YAP1 expression was correlated with cytoplasmic localization (hereafter referred to as YAP1 low). These findings are consistent with those of the previous report ( 20 , 21 ).…”
Section: Resultssupporting
confidence: 94%
“…These conjunctival and corneal cellular responses in horses with OSSN likely reflect inflammation associated with immune responses to the malignant cells. For example, previous histological studies of equine OSSN have demonstrated an inflammatory cell infiltrate in most of the tumor biopsies that were examined, indicative of an ongoing anti-tumor immune response [59,60]. In addition to the plethora of immune pathways, cilium assembly was downregulated in OSSN eyes, which is in line with previous reports of dysregulation in ocular diseases [61].…”
Section: Discussionsupporting
confidence: 85%
“…During our previous investigation, exploring the potential associations between oncogenic viruses and ocular surface squamous neoplasia (OSSN) (Julius et al, 2021;Julius et al, 2022;Julius et al, 2023), we encountered a patient with ocular KS among our cohort of 458 patients recruited with ocular surface tumors at the University Teaching Hospitals (UTH) Eye Hospital in Lusaka, Zambia. As an incidental finding, the ocular surface KS tumor analysis revealed the co-infection and co-localization of KSHV and EBV.…”
Section: Introductionmentioning
confidence: 99%